Predictors for Prolonged Hospital Stay Solely to Complete Intravenous Antifungal Treatment in Patients with Candidemia: Results from the ECMM Candida III Multinational European Observational Cohort Study - Matthias Egger; Jon Salmanton-García; Aleksandra Barac; Jean-Pierre Gangneux; Hélène Guegan; Valentina Arsic-Arsenijevic; Tadeja Matos; Rok Tomazin; Nikolai Klimko; Matteo Bassetti; Helena Hammarström; Eelco F. J. Meijer; et al. (Mycopathologia, 2023)
Background To date, azoles represent the only viable option for oral treatment of invasive Candida infections, while rates of azole resistance among non-albicans Candida spp. continue to increase. The objective of this sub-analysis of the European multicenter observational cohort study Candida III was to describe demographical and clinical characteristics of the cohort requiring prolonged hospitalization solely to complete intravenous (iv) antifungal treatment (AF Tx). Methods Each participating hospital (number of eligible hospitals per country determined by population size) included the first ~ 10 blood culture proven adult candidemia cases occurring consecutively after July 1st, 2018, and treating physicians answered the question on whether hospital stay was prolonged only for completion of intravenous antifungal therapy. Descriptive analyses as well as binary logistic regression was used to assess for predictors of prolonged hospitalization solely to complete iv AF Tx. Findings Hospital stay was prolonged solely for the completion of iv AF Tx in 16% (100/621) of candidemia cases by a median of 16 days (IQR 8 – 28). In the multivariable model, initial echinocandin treatment was a positive predictor for prolonged hospitalization to complete iv AF Tx (aOR 2.87, 95% CI 1.55 – 5.32, p < 0.001), while (i) neutropenia, (ii) intensive care unit admission, (iii) catheter related candidemia, (iv) total parenteral nutrition, and (v) C. parapsilosis as causative pathogen were found to be negative predictors (aOR 0.22 – 0.45; p < 0.03). Interpretation Hospital stays were prolonged due to need of iv AF Tx in 16% of patients with candidemia. Those patients were more likely to receive echinocandins as initial treatment and were less severely ill and less likely infected with C. parapsilosis .

Overview of the search for signs of space weathering on the low-albedo asteroid (101955) Bennu - B.E. Clark; A. Sen; X.-D. Zou; D.N. DellaGiustina; S. Sugita; N. Sakatani; M. Thompson; D. Trang; E. Tatsumi; M.A. Barucci; M. Barker; H. Campins; et al. (Icarus, 2023)